The Changing Nature of Technology Shocks - Christoph Görtz; Christopher Gunn; Thomas A. Lubik (CESifo GmbH, 2024)
We document changes to the pattern of technology shocks and their propagation in post-war U.S. data. Using an agnostic identification procedure, we show that the dominant shock driving total factor productivity (TFP) is akin to a diffusion or news shock and that shock transmission has changed over time. Specifically, the behavior of hours worked is notably different before and after the 1980s. In addition, the importance of technology shocks as a major driver of aggregate fluctuations has increased over time. They play a dominant role in the second subsample, but much less so in the first. We build a rich structural model to explain these new facts. Using impulse-response matching, we find that a change in the stance of monetary policy and the nature of intangible capital accumulation both played dominant roles in accounting for the differences in TFP shock propagation.
Keywords: E20; E30; 330; technology shocks; TFP; business cycles; shock transmission